Effects of moderate magnesium application on rice milling quality, nutritional value and eating quality - Yongbing Wang; Zhaohui Ma; Haitao Cheng; Wenyan Lyu; Dong Wang (Frontiers in Sustainable Food Systems)
BackgroundMagnesium (Mg), an essential secondary macronutrient for plant growth and development, and its dose–response relationships with crop yield and quality remain to be systematically characterized.MethodsThe experiment was conducted at Shenyang Agricultural University using the locally predominant rice cultivar “Liaojing 294.” A randomized block design was employed with four magnesium (Mg) treatment levels: Mg0 (no Mg), Mg1 (14.72 kg ha−1), Mg2 (29.43 kg ha−1), and Mg3 (44.15 kg ha−1). This study aimed to investigate the effects of Mg application rates on rice yield components, milling quality, cooking/eating quality, and nutritional composition.Results(i) Mg application enhances yield per unit area by promoting tillering into panicles and grain filling; (ii) Mg improves rice pasting properties and eating quality; (iii) Moderate Mg application (29.43 kg ha−1) significantly increased grain protein content, while further increasing Mg rate (44.15 kg ha−1) resulted in decreased protein content but a significant rise in sucrose content; (iv) The pasting temperature and peak time were closely associated with soluble sugar content, exhibiting significant positive correlations with glucose and sucrose contents, respectively.ConclusionWhen the Mg application rate was 29.43–44.15 kg ha−1, rice yield, processing quality, nutritional value, and palatability were significantly improved.